2012
DOI: 10.1037/a0025956
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal investigation of the impact of disordered eating on young women's quality of life.

Abstract: Objective: The extent to which subclinical levels of disordered eating affect quality of life (QOL) was assessed. Method: Four waves of self-report data from Survey 2 (S2) to 5 (S5) of a national longitudinal survey of young Australian women (N = 9,688) were used to assess the impact of any level of disordered eating at S2 on QOL over the following 9 years, and to evaluate any moderating effects of social support and of depression. Results: At baseline, 23% of the women exhibited some level of disordered eatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
76
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 30 publications
5
76
0
1
Order By: Relevance
“…Few studies have considered the developmental trajectory of eating disorder symptoms in males, but available data suggest that boys may show reductions in eating pathology from early adolescence to mid adolescence, and then experience an increase in symptoms in late adolescence or early adulthood [3,5,7,8]. Eating disorder symptoms are associated with impairments in quality of life even when full criteria for an eating disorder are not met [9-11]. This makes it important that they are considered in research on the epidemiology and consequences of eating disorder psychopathology.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have considered the developmental trajectory of eating disorder symptoms in males, but available data suggest that boys may show reductions in eating pathology from early adolescence to mid adolescence, and then experience an increase in symptoms in late adolescence or early adulthood [3,5,7,8]. Eating disorder symptoms are associated with impairments in quality of life even when full criteria for an eating disorder are not met [9-11]. This makes it important that they are considered in research on the epidemiology and consequences of eating disorder psychopathology.…”
Section: Introductionmentioning
confidence: 99%
“…1), finding evidence for complementary mediation in a sample of female university students. Complementary or competitive mediation in the presence of a significant direct effect suggests that other mediators may be present (Zhao et al, 2010); such variables might include personality traits (Fischer et al, 2007), anxiety, depression (Wade et al, 2012), employment status, and self-esteem (de la Rie et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…A recent longitudinal study by Wade et al (2012) of a large community sample of Australian women found that even subclinical levels of symptoms are associated with lasting deficits in well-being. They found that disordered eating predicted later impairments in quality of life (QoL), spanning a period of 9 years, although it was not possible to assess what proportion (if any) of these women had received treatment.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The eating disorder diagnoses are based on specified levels of frequency and severity of disordered eating behaviors (DEB). However, erratic patterns of DEB at levels as low as “at least once over the last year” persist for periods as long as ten years [3], and predict compromised physical and emotional health [4] and short and long-term weight gain [5]. In the study described here we test the hypothesis that DEB are correlated with level of tobacco and alcohol use in young adult Mexican American (MA) women, a pattern of risk behaviors demonstrated in both clinical and community based majority samples.…”
Section: Introductionmentioning
confidence: 99%